Semiconductor Integrated Optics for Switching Light - Ironside, Charlie (2017)
The nonlinear integrated Mach-Zehnder was also configured as an asymmetric device. For the AMZI device of length around 0.5 cm, the input intensities required to switch are around 2×109 W cm-2, which implies optical pulse energies of ...